Atomic resolution STM of the NiO(001) surface structure and defect sites: c(2x2) patterning and effects of covalent bonding - Castell, M; Dudarev, S; Wincott, P; Condon, N; Muggelberg, C; Thornton, G; Manh, D; Sutton, A; Briggs, G (1997)
Elevated temperature STM has been used to obtain atomic resolution images of flat regions, defect sites and step edges on the (001) surface of crystalline nickel oxide. Identification of surface lattice sites seen in empty and filled states (nickel and oxygen sites, respectively) is consistent with recent theoretical results according to which NiO is a charge transfer insulator with strongly correlated electrons. It has been found that certain surface defects lead to the formation of spatially delocalized hole states resulting in c(2 x 2) patterning in STM images. The appearance of this patterning points to the presence of a substantial covalent contribution to chemical bonding in NiO.